A novel method for pair-matching using three-dimensional digital models of bone: mesh-to-mesh value comparison. - Karell, Mara A; Langstaff, Helen K; Halazonetis, Demetrios J; Minghetti, Caterina; Frelat, Mélanie; Kranioti, Elena F (Int J Legal Med, 2016)
The commingling of human remains often hinders forensic/physical anthropologists during the identification process, as there are limited methods to accurately sort these remains. This study investigates a new method for pair-matching, a common individualization technique, which uses digital three-dimensional models of bone: mesh-to-mesh value comparison (MVC). The MVC method digitally compares the entire three-dimensional geometry of two bones at once to produce a single value to indicate their similarity. Two different versions of this method, one manual and the other automated, were created and then tested for how well they accurately pair-matched humeri. Each version was assessed using sensitivity and specificity. The manual mesh-to-mesh value comparison method was 100 % sensitive and 100 % specific. The automated mesh-to-mesh value comparison method was 95 % sensitive and 60 % specific. Our results indicate that the mesh-to-mesh value comparison method overall is a powerful new tool for accurately pair-matching commingled skeletal elements, although the automated version still needs improvement.
Keywords: Adult; computer simulation; Female; Forensic Anthropology; Humans; Humerus; Imaging, Three-Dimensional; Male; Tomography, X-Ray Computed